Reconceptualising intellectual capital in the era of artificial intelligence - Idris, Asma’ Rashidah; Muda, Salwa; Mat Nawi, Hafizah; Musman, Musliha; Mohamed Sadique, Raziah Bi; Ismail, Norhidayah; Hussin, Amariah Hanum (International Journal of Accounting, Finance and Business, 2026)
The rapid advancement of Artificial Intelligence (AI) is redefining the architecture of organizational knowledge and challenging traditional conceptualizations of intellectual capital (IC). While IC has long been recognized as a key driver of firm performance, its conventional framework that centered on human, structural, and relational capital remains largely static and insufficient in capturing the dynamic, data-driven realities of modern organizations. This paper develops a conceptual perspective that positions AI as an embedded and transformative capability that reconfigures the foundations of IC. Drawing on the Resource-Based View (RBV) and Knowledge-Based View (KBV), the paper argues that AI enhances the scalability, adaptability, and productivity of intellectual resources. By critically contrasting traditional and AI-enabled IC, this study advances a more integrative framework that reflects the evolving nature of knowledge ecosystems. The paper concludes by outlining future research directions and highlighting implications for SMEs in emerging economies.